Declining Exhaustible Resource Rent with Small, Distinct Extractive Firms - John Hartwick; Andrei Bazhanov; Zhen Song (Queen's University, Department of Economics, 2007)
We consider a competitive extraction industry comprising many small firms, each with a slightly different quality of mineral holdings. With "rapidly" declining quality of holding per firm we observe rent declining over and interval. We do not work with the planning solution, commonly invoked in the study of firms with distinct qualities of stock.
Keywords: Q31; D41; 330; exhaustible resources; resource rent; competitive extraction; Erschöpfbare Ressourcen; Rohstoffwirtschaft; Bergbau; KMU; Gewinn; Unternehmenserfolg